Improving the through‐thickness electrical conductivity of carbon fiber reinforced polymer composites using interleaving conducting veils. Issue 43 (27th August 2022) - Waqas, Muhammad; Robert, Colin; Arif, Urwah; Radacsi, Norbert; Ray, Dipa; Koutsos, Vasileios
Abstract: In this study, thin carbon fiber‐based conducting veils were used as interleaving materials to improve the through‐thickness electrical conductivity of carbon fiber reinforced composites. Carbon fiber (CF) or nickel‐coated carbon fiber (NiCF) veils were used as interlayers between standard carbon fiber reinforcement fabrics. The through‐thickness electrical conductivity of the interleaved composites with CF or NiCF veils improved over 50 fold, from 0.18 to 9.47 and 9.16 S/cm, respectively, compared to the control specimens. However, the interleaved specimens exhibited a ca. 20%–24% reduction in their interlaminar shear strength (ILSS) and flexural strength. The introduction of conducting veils facilitated establishing an electrical pathway between the carbon fabric plies by reducing the non‐conducting resin rich zone in the interlaminar region. This established an electrically conductive pathway across the thickness of the laminate. This study reveals that conducting veil‐interleaved composites can meet a functional integration requirement of the aerospace sector for electrical properties, and can find applications in lightning protection, EMI shielding, and structural health monitoring. Abstract :